Detailed Seismic Performance Assessment of High-Value-Contents Laboratory Facility. Issue 4 (November 2015) - Yang, T. Y.; Atkinson, J. C.; Tobber, L.
Recent earthquakes worldwide have shown that even countries with well-established building codes are still vulnerable to economic and societal losses. To properly assess these seismic losses, risk managers and insurers need a well-defined tool to quantify the seismic performance of the facilities. In this paper, detailed performance-based earthquake engineering methodology is applied to assess the seismic vulnerability of a high-value-contents laboratory facility, in Vancouver, Canada. The study demonstrates a detailed implementation of the state-of-the-art performance assessment tools to quantify the seismic loss of facilities that can be readily used by practicing engineers. The results show the first benchmark study to quantify the performance of code-based design and provide valuable information for engineers and facility stakeholders to make informed risk-management decisions.